Maturing Masculinities : Aging, Chronic Illness, and Viagra in Mexico - Wentzell, Emily A., 1980- (Book collections on Project MUSE., 2013)
Based on interviews with male patients in a urology clinic in Cuernavaca, Maturing Masculinities offers an exploration of how older men in urban Mexico incorporate aging and decreasing erectile function into their conceptions of themselves as men.